Ethnobotanical and ethnopharmacological documentation of antimalarial plants used by the Jakun community in Kg Peta, Endau-Rompin, Johor, Malaysia - Ismail, Izdihar (2017)
Malaria, one of the leading infectious diseases in many tropical regions including Malaysia is caused by the parasite Plasmodium. An ethnobotanical survey of medicinal plants used by the indigenous people particularly the Jakun tribe from Kg. Peta, Endau-Rompin, Johor for the treatment of malaria and malaria associated symptoms was conducted using a semi-structured interview. The declining popularity of application of traditional remedies by the young generation threatens the disappearance of traditional knowledge possessed mainly by the older generation. Hence, the need for documentation of this knowledge justifies the relevance of this study. Out of 19 species (17 families) were recorded, 7 species: Hodgsonia macrocarpa, Pentaphragma begoniifolium, Rennellia elliptica, Saprosma corymbosa, Strychnos ignatii, Tacca integrifolia and Tetracera macrophylla were investigated for phytochemical and in vitro antiplasmodial activities. Twelve aqueous and 12 methanolic extracts were screened for antiplasmodial phytochemical classes i.e., alkaloids, flavonoids, terpenoids and anthraquinones using thin-layer chromatography (TLC). Results revealed the presence of at least one of the phytochemical class in each extracts. Extracts were subjected to antiplasmodial activity through histidine-rich protein II (HRP2) assay against K1 strain of P. falciparum chloroquine-resistant. Overall, ten methanolic extracts from H. macrocarpa (stem), P. begoniifolium (root, stem and leaves), R. elliptica (root, stem and leaves), S. corymbosa (leaves), T. integrifolia (root) and T. macrophylla (stem) have potential antiplasmodial activities against chloroquine-resistant P. falciparum (IC50 < 10 μg/mL). The part of the plants species involves indicates statistically significant difference of IC50 between the kinds of extractions (p < 0.05). The results scientifically validated the plants used in Jakun’s traditional medicine displayed promising therapeutic properties and further studies could lead to develop phytomedicines in the treatment of malaria.